AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Widhiastuti, Ni Luh Putu (Fakultas Ekonomi, Universitas Semarang, 2022)
This study aims to determine the effect of audit committee competence, number of audit committee members, audit committee meetings, audit committee independence and audit opinion on audit delay in manufacturing companies listed on the Indonesia Stock Exchange. The population in this study were 165 manufacturing companies listed consecutively on the Indonesia Stock Exchange. The sampling method used in this study was purposive sampling, with a research of 300 companies during the period 2018-2020. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that the competence of the audit committee has a positive effect on audit delay. The number of audit committee members and audit opinion has a negative effect on audit delay. Meanwhile, audit committee meetings and audit committee independence have no effect on audit delay. Further research can develop this research by using other variables that in theory have an influence on audit delay, such as audit tenure.